Karakteristik Selai Lembaran Kolang-Kaling dengan Penambahan Buah Naga Merah - Ranita Sari; Vonny Setiaries Johan; Noviar Harun (Universitas Djuanda, 2020)
The purpose of this research was to obtain the best formulation of slice jam from kolang-kaling and red dragon fruit based on the characteristics. This research used experimental method by using a complete randomized design (RAL) with four treatments and four replications. The treatments were KN1 = kolang-kaling puree 90% and red dragon fruit puree 10%, KN2 = kolang-kaling puree 80% and red dragon fruit 20%, KN3 = kolang-kaling puree 70% and red dragon fruit puree 30%, KN4 = kolang-kaling puree 60% and red dragon fruit puree 40%. Data were statistically analyzed using ANOVA and DNMRT at 5% level. Based on this research the best treatment was slice jam KN3= kolang-kaling puree 70% and red dragon fruit puree 30% which had 19,55% moisture content, 0,55% ash content, 1,52% crude fiber content, 41,45% level of reducty sugar. Result of the sensory test were descriptive red colorur, kolang-kaling and red dragon fruit taste, red dragon fruit flavor, and rather chewy in texture. Result of the hedonic test on color, taste, flavor, texture and overall assessment were liked by panelists.